INTEGERASI HOLISTIK INDUSTRY 4.0 DAN HUMAN RESOURCE INFORMATION SYSTEM (HRIS) MENUJU STRATEGIC HUMAN RESOURCE MANAGEMENT (SHRM) BERBASIS NILAI: ANALISIS KOMPARATIF DAMPAK DIGITALISASI PADA EFEKTIVITAS FUNGSI SDM STRATEGIS - Muhammad Gajali; Khuzaini; Syahrial Shaddiq (PT. Saha Kreasi Indonesia, 2025)
The rapid escalation of the Industrial Revolution has positioned digital transformation as a strategic imperative across industries, significantly influencing the fundamental reorientation of Human Resource Management (HRM) practices. This study aims to provide a comparative analysis of how digitalization—particularly through the adoption of Industrial 4.0–based Human Resource Information Systems (HRIS)—enhances the effectiveness of Strategic Human Resource Management (SHRM) functions. Using a systematic literature review and qualitative descriptive analysis, this research synthesizes conceptual frameworks, functional impacts, and implementation challenges. The results indicate that HRIS 4.0 functions as a transformative infrastructural bridge that requires integration within a holistic framework aligned with the efficiency demands of Industry 4.0 and the human-centered principles of Society 5.0. Core SHRM functions have undergone significant metamorphosis due to advancements in AI and data analytics, contributing to operational improvements—particularly enhancing recruitment efficiency by up to 67%. Nevertheless, implementation challenges persist, including digital skill gaps and data security risks. Therefore, sustaining SHRM effectiveness in this era requires the ethical alignment of HRIS 4.0, positioning HR professionals—especially HR Business Partners (HRBPs)—as strategic catalysts who leverage AI-driven strategies while maintaining a strong focus on human capability development and value creation.